Beta cell protective effect of Curcuma longa and Piper nigrum in cytokine cocktail induced apoptosis in Min6 pancreatic beta cells - Hemangee Damame; Sheetalnath Rooge; Rahul Patil; Chandramukhi Garad; Akalpita Arvindekar (Elsevier, 2021)
Background: : Type 1 diabetes mellitus is characterized by loss of beta cell mass and insulin insufficiency. Beta cell apoptosis and destruction by cytotoxic T lymphocytes and pro-inflammatory cytokines like IL-1β, TNF-α and IFN-γ appears to represent a key event in pathogenesis of type 1 diabetes mellitus. Purpose: : The aim of present study was to evaluate the prophylactic effect of aqueous extract of Curcuma longa and Piper nigrum (CL-PN) in ratio 2:1 on pancreatic beta cell apoptosis and dysfunction induced by cytokine cocktail of IL-1β (50 ng/ml), TNF-α (25 ng/ml) and IFN-γ (25 ng/ml). Methods: : We used Min6 beta cell line as an in vitro model and the cells were pre-treated with herbal extract of CL-PN and then exposed to cytokine cocktail for 6 hrs to mimic beta cell destruction as in type 1 diabetes. Beta cell apoptosis and protective activity were assessed by flow cytometer based assay of annexin-V FITC and propidium iodide staining. Results: : Aqueous extract of the combination of CL-PN at 1 μg/ml concentration can effectively inhibit apoptosis in Min6 beta cell line by 1.6 fold as compared to cytokine cocktail. It also demonstrated 2.6 fold lesser production of nitric oxide, 1.4 fold reduced ROS and increasing mitochondrial membrane potential which are major markers of beta cell damage. The caspase 3 mRNA expression is also reduced by 4.7 fold despite cytokine challenge. Conclusion: : Therefore, the present study paves the way for establishing herbal oral treatment for protection of beta cells in type 1 diabetes mellitus.